Pengaruh Model Pembelajaran Berbasis Masalah dengan Pendekatan Problem Posing terhadap Kreativitas Matematika dan Aktivitas Siswa Pada Materi Kubus dan Balok Kelas VIII SMP Negeri 7 Polewali - Ahmad Syah; Alimuddin Alimuddin; Ahmad Talib (Fakultas Keguruan dan Ilmu Pendidikan Univ. Al Asyariah Mandar Sulbar, 2019)
The research aims on discovery the description and the influence of Problem Based Learning Model with Problem Posing Approach on mathematics creativity and Student Activity on The Material of Cubes and Beams of Class VIII Student at SMPN 7 Polewali. The research was free experiment research which employed one group pretest-posttest design. The result of research reveal that (1) the student’ Mathematics creativities before applying problem based learning with problem posing approach to class VIII B student at SMPN 7 Polewali show that 23 student are in uncreative category and 1 student is less creativity category, the student’ mathematics creativity after applying problem based learning with problem posing approach to class VIII B student at SMPN 7 Polewali shows that 1 student is in very creativity, 5 student are in creativity category, 17 student are in fairly creative category and 1 student is in less creativity category, (2) the description of the students’ learning activity after applying problem based learning with problem posing approach to class VIII B student at SMPN 7 Polewali overall is in active category, (3) problem based learning with problem posing approach gives influence to class VIII B student at SMPN 7 Polewali with gain score in medium category.